Producción y descomposición del mantillo en un bosque secundario húmedo de premontano - Fournier, Luis A. (1973)
Litter production and decomposition were studied from March, 1971 to January, 1972 in a Premontane Moist Secondary Forest at San Pedro de Montes de Oca, Costa Rica, 1,200 m above sea level.The forest produced a monthly average of 2,246.10 kg/ha of litter (dry basis); the higher yield oecurred during the dry season (November early May). It was due, mostly, to the faet that the dominant species of this forest are deciduous, and that most other species lose a great proportion of their foliage in this season.About 57.48% of lilter is composed of litter is composed of leaves, 38,10% branches, flowers and fruits contribute 1.65% and 1.98%, respectively.The rate of lilter decompo,ition is, as in most tropical regions, relatively fast during the rainy season; however, specific differences were observed. Lilter from pioneer species tends to decay more rapidly. Lilter composition apparently matehes the floristic composition of the forest and the phytosociological importance of the species. The dominant species seem to be more frequently represented in the forest, but this aspect deserves more research.